National culture dimensions: The perpetuation of cultural ignorance. Issue 5 (November 2016) - Venaik, Sunil; Brewer, Paul
The Hofstede and GLOBE national culture dimensions are commonly used by business and management educators, researchers and practitioners to understand cultural differences between countries. However, there are fundamental problems in using these dimensions to learn about cross-cultural differences. First, there is a lack of face validity in many of the items used to determine the culture scores. Second, national culture scores for similar dimensions across the two models for common countries are either unrelated or negatively related, and for dissimilar dimensions are often more strongly related than for the similar dimensions. A lack of face, convergent and discriminant validity seriously undermines the credibility of the dimension scores in representing the culture phenomena that they claim to represent. Hence, using these scores to infer the broader characteristics of societies, individuals and organizations is invalid and the managerial prescriptions based on such research are misleading. As cross-cultural learning in management is largely shaped by national culture models, the blind faith in these models is perpetuating cultural ignorance.